National law of the deceased, party autonomy and renvoi. A play in three acts. Comments on the spanish supreme court judgement of 15th January 2019 - Carrascosa González, Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
This work makes a critical and positive reading of several elements than may be found in the Spanish Supreme Court case law, such as the role of the National Law in international successions, renvoi at first degree, and the party autonomy of the deceased with regard to the law governing succession. The apper highlights that renvoi at first degree, understood in a selective sense, can be used to achieve the application of the Law of the country most connected to an international succession in cases in which the country of the nationality of the deceased does not maintain a substantial link with the case.